Low-temperature magnetic and thermal properties of the frustrated two-dimensional S = 1 compound Ni₅(TeO₃)₄Cl₂ - Khatsko, E.; Nizhankovskii, S.V.; Gnatchenko, S.; Zaleski, А.; Lemmens, P.; Berger, H. (Физика низких температур, 2011)
The temperature and magnetic field dependent magnetization of the two-dimensional quantum spin system Ni₅(TeO₃)₄Cl₂ has been investigated using single crystals in temperature range 1.8–100 K and in magnetic fields up to 14 T. The magnetization below the magnetic phase transition demonstrates an unusual temperature behavior with considerable anisotropy. Combined magnetization and specific heat data allowed to determine the critical temperature of the magnetic phase transition, Tc = 28.4 K. Magnetic fields shift this temperature toward lower temperatures.